2004
DOI: 10.1007/s00420-004-0521-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunological biomarkers in salt miners exposed to salt dust, diesel exhaust and nitrogen oxides

Abstract: Significant differences between non-smokers and active smokers were found for most of the leukocyte types (e.g. granulocytes P = 0.000, lymphocytes P = 0.002, T-cells P = 0.033) and for some soluble parameters (ICAM P = 0.000, IgM P = 0.007, IgE P = 0.035). Increasing numbers of total lymphocytes, T-cells and HLA-DR positive T-cells in relation to exposure were found by linear regression analysis (e.g. for inhalable dust:total lymphocytes P = 0.011, T-cells P = 0.061, HLA-DR positive T-cells P = 0.007). CONCLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…There are few previously published data with which to compare the results of our study. However, recent studies have reported personal EC measurement levels between 20 and >500 μg m −3 (Ramachandran and Watts, 2003; Backe et al , 2004; Birch and Noll, 2004; Adelroth et al , 2006; Burgess et al , 2007; Dahmann et al , 2007; Noll et al , 2007). The wide range among these studies is likely due to different types and amounts of diesel equipment, airflow rates, and work practices, just as these differences influenced exposure levels in our facilities.…”
Section: Discussionmentioning
confidence: 99%
“…There are few previously published data with which to compare the results of our study. However, recent studies have reported personal EC measurement levels between 20 and >500 μg m −3 (Ramachandran and Watts, 2003; Backe et al , 2004; Birch and Noll, 2004; Adelroth et al , 2006; Burgess et al , 2007; Dahmann et al , 2007; Noll et al , 2007). The wide range among these studies is likely due to different types and amounts of diesel equipment, airflow rates, and work practices, just as these differences influenced exposure levels in our facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as harmful habits (tobacco smoking and alcohol consumption) can also influence the changes of parameters of cellular immunity (18,19). In the case of advanced cancer, these changes in parameters are basically affected by disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies have shown a greater risk for respiratory symptoms among asphalt workers than for road maintenance workers (8). Adverse respiratory effects and systemic inflammatory responses in workers exposed to dusts and fumes have recently been reported for several different occupations, for example, welders (9), firefighters (10,11) salt miners (12), and tunnel workers (13)(14)(15).…”
mentioning
confidence: 99%